The darker side of high performance work systems: Examining employee psychological outcomes and counterproductive work behavior - Sumaira Gulza; Moin Ahmed Moon; Saman Attiq; Rauf I. Azam (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The purpose of this paper is to analyze the impact of the employee perception about high performance work systems (HPWS) on employee psychological outcomes and further their impact on counterproductive work behavior. After reviewing the literature on rhetoric versus reality of HPWS, the potential "dark side" of HPWS authors suggested that HPWS, aimed at creating a competitive advantage for organizations, do so at the expense of workers, thus resulting in negative consequences for individual employees. This paper analyzes these relationships using a total sample of 287 from firms operating in Pakistan. Findings revealed that employee perception about HPWS are positively associated with employee psychological outcomes (anxiety, job burnout, role overload) which further results in a negative behavior of the employees at workplace. One of the main limitations of this paper is the cross-sectional design of the empirical research and the fact that data were collected from managerial staff only. Findings may guide managers' efforts in the development of learning programs which foster both individual and organizational performance. Finally, the paper provided empirical evidence of the proposed relationships in Pakistan.
Keywords: 330; high performance work system; psychological outcomes; anxiety; job burnout; role overload; counterproductive work behavior and Pakistan